Higher education in India : in search of equality, quality and quantity - Tilak, Jandhyala B. G. (New Delhi : Orient Blackswan, 2013)
Contributed articles.
Section 1. Democracy, equality and universality -- section 2. Equality to inclusion in higher education -- section 3. Excellence in higher education -- section 4. Case studies on higher education -- section 5. Public expenditure on education -- section 6. State, markets and globalisation -- section 7. Towards reforming higher education.
"EPW, Tata Institute of Social Sciences."
"Essays from Economic and political weekly"--Cover.
Includes bibliographical references.
Keywords: Education, Higher -- India